PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Verina Greselda br. Simbolon; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the effect of receivables turnover and inventory turnover on the profitability of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The independent variables in this study are accounts receivable turnover and inventory turnover. The dependent variable in this study is profitability. The research population is the pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2016-2020 period. The sampling technique used is purposive sampling technique. Based on the established criteria, a sample of 7 companies from 11 existing sub-sector copmpanies was obtained. The type of data used is secondary data. This research uses quantitative methods with SPSS (Statistical product and service solutions). The results showed that there was an influence between accounts receivable turnover and inventory turnover on profitability, either partially or simultaneously tested. Keywords: Accounts Receivable Turnover, Inventory Turnover, Profitability